2018
DOI: 10.1177/0081246318757932
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the South African work on the well-being of young people (2000–2016)

Abstract: Burgeoning research on the well-being of young people in recent years has made it difficult to identify conceptual gaps in the literature. We conducted a review of South African research in this area to better understand the use and measurement of the construct, as well as factors associated with it. The search of multiple databases identified 28 studies published in academic journals between 2000 and 2016. Within this period, studies that referred to well-being and its related subjective components varied sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Even the intention to use contraceptives improves the health of children, women, families, and whole societies [ 7 ]. In sub-Saharan Africa, unintended pregnancies, high fertility, and abortion are still challenges for women of reproductive age [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even the intention to use contraceptives improves the health of children, women, families, and whole societies [ 7 ]. In sub-Saharan Africa, unintended pregnancies, high fertility, and abortion are still challenges for women of reproductive age [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In SSA, most young people are growing up in poor settings that are associated with high unemployment rates, rapid urbanization, often limited educational opportunities, and rapidly changing socio-cultural norms and practices [5,6]. Apart from these general challenges, the female population has to do deal with several sexual and reproductive issues, including unintended pregnancies, high fertility and abortions [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…14 A systematic review of studies in South Africa indicated increasing interest and work on wellbeing of young people in that country. 15 In the United Kingdom, the Office for National Statistics regularly reports on the wellbeing of children and adolescents up to age 15 years, using 31 indicators across seven domains. 16 We found no single example of a comprehensive measurement approach aligned with the Adolescent Wellbeing Framework.…”
Section: Current Measurement Approaches Are Fragmentedmentioning
confidence: 99%